Skoolgebaseerde Selfevaluering as ’n Evalueringsmetode vir Gebruik in Christelike Privaatskole - van Niekerk, E. J. (Tydskrif vir Christelike Wetenskap | Journal for Christian Scholarship, 2003)
As a result of a well executed self-evaluation school improvement and development can be brought about. For Christian private schools to benefit the most from the advantages of self-evaluation, they need to empower themselves to do independent school-based self-evaluation. In this article a christian point of departure for self-evaluation is discussed, and possible areas for self-evaluation, the focal point of self-evaluation and the participants in self-evaluation are indicated. Finally a possible strategy for self-evaluation is suggested.